The contradictions of export-led growth - Thomas I. Palley (Levy Economics Institute of Bard College, 2011)
The export-led growth paradigm is a development strategy aimed at growing productive capacity by focusing on foreign markets. It rose to prominence in the late 1970s and became part of a new consensus among economists about the benefits of economic openness. According to Thomas I. Palley, this paradigm is no longer relevant because of changed conditions in both emerging-market (EM) and developed economies. He outlines the stages of the export-led growth paradigm leading to its adoption worldwide, as well as the various critiques of this agenda that have become increasingly prescient. He concludes that we should reduce reliance on strategies aimed at attracting export-oriented foreign direct investment and institute a new paradigm based on a domestic demand-led growth model. Otherwise, the global economy is likely to experience asymmetric stagnation and increased economic tensions between EM and industrialized economies.
Keywords: 330